Bridging the gap: The need for a systems thinking approach in understanding and addressing energy and environmental performance in buildings. Issue 1 (January 2019) - Shrubsole, C.; Hamilton, I. G.; Zimmermann, N.; Papachristos, G.; Broyd, T.; Burman, E.; Mumovic, D.; Zhu, Y.; Lin, B.; Davies, M.
Innovations in materials, construction techniques and technologies in building construction and refurbishment aim to reduce carbon emissions and produce low-energy buildings. However, in-use performance consistently misses design specifications, particularly those of operational energy use and indoor environmental quality. This performance gap risks reducing design, technology, sustainability, economic, health and well-being benefits. In this paper, we compare settings of the Chinese and the UK buildings sectors and relate their historical context, design, construction and operation issues impacting energy performance, indoor environmental quality, occupant health and well-being. We identify a series of key, common factors of 'total' building performance across these two settings: the application of building regulations, the balance between building cost and performance, skills, construction and operation. The dynamic and complex interactions of these factors are currently poorly understood and lead to building performance gaps. We contend that a systems approach in the development of suitable building assessment methods, technologies and tools could enable the formulation and implementation of more effective policies, regulations and practices. The paper illustrates the application of the approach to the UK and Chinese settings. A full application of a systems approach may help to provide a more dynamic understanding of how factor interactions impact the 'total' building performance gaps and help address its multiple causes.